The relation of minority group’s sport attainment to counter racism: African-American at the movie 42 - Triastama Wiraatmaja (EduLite: Journal of English Education, Literature and Culture, 2019)
This study was conducted to determine the efforts made by minority groups who are being oppressed by racism based on context-relationship of African Americans at the movie 42 (2013). Findings of this article based on qualitative studies with auteur theory, and mise-en scene, undertaken in movie 42 (2013) regarding racism towards minority groups, African-American, and by implementing thick description the researcher highlighted minority group’s achievement’s at the movie 42 in the field of Sports and the relation to life-betterment. The result revealed that racism towards minority group had emerged because of the so-called white’s supremacy concept. This study found that African American as minority group were able to alter their life despite of racism through equal sport’s opportunity. Besides, this study has highlighted one pivotal area in which any minority group should concern to enhance their life; sports. Moreover, even though this study focusing more on the relation of the effort’s made by minority group at America, this study illustrates the importance of having initiatives in providing better opportunity related to sports to ensure a better life opportunity among minority groups all over the globe.